Impact of Nodes on Energy Consumption of IoT Devices - Yuslinda Wati Mohamad Yusof; Kassim, Murizah; Nurul Hanani Azmi; Mohd Nazri Ismail (International Journal of Integrated Engineering, 2024)
The rapid growth of the Internet of Things (IoT) has raised concerns about energy consumption in IoT devices, significantly influenced by the number of network nodes. This research investigates the impact of nodes contributing to the highest and lowest energy consumption of IoT devices and analyze energy consumption based on battery model in IoT devices. A simulation model is created using Network Simulator Tool (NetSim) with four types of lithium-ion batteries and 3 nodes configuration: 5, 10 and 15 nodes. Results show that, for a 5-node setup with a 3000mAh 3.7V design, the lowest energy consumption value is 2.6634 kJ and the highest remaining energy value is 93.33% occur after 12 hours. For 10 nodes, energy consumption is 5.3497kJ with remaining energy is 86.61%. While for 15 nodes, the highest energy consumption is 8.0542kJ and the remaining energy is 79.84%. The study concludes that more nodes lead to higher energy consumption due to increased computing load, network traffic, and resource utilization. It is also highlighting that prolonged activation of nodes leads to higher batter consumption, emphasizing the need for efficient power management in IoT devices.